Assessment of using shungite rock technological feasibility in the production of manganese agglomerate (Modern Problems of Metallurgy, 2022)
Industrial experience in the production of manganese sinter shows that the known technological proposals do not provide an increase in the productivity of sintering machines and the necessary strength properties of fluxed manganese sinter. Known methods of sintering fluxed manganese agglomerate, characterized by increased mechanical strength and high moisture resistance. The disadvantage of these measures is a significant complication of the technological line of sinter production and an increase in energy costs. In this regard, one of the main directions is the development of charge compositions and parameters of the sintering process of manganese raw materials. The purpose of the study is the analysis of physical and chemical processes, experimental research and the development of innovative technological solutions and recommendations for attracting shungite rock to the metallurgical production to expand the raw material base of the mining and metallurgical complex. Calculations of the thermodynamic equilibrium of oxide systems adequate to sinter systems have been performed, and the chemical composition of the phase components of manganese agglomerate microstructures has been studied. The rational content of shungite in the sinter charge has been established, which ensures the production of agglomerate with specified characteristics (strength, usable yield, manganese content) is 12...13% of the mass of the initial charge. A further increase in its particles in the sinter mixture leads to a decrease in strength and the release of suitable heat. Increasing the degree of dispersion of shungite to 0-2 mm allows increasing the level of use of shungite carbon as a fuel without increasing the amount of traditional fuel - coke - for the process.